Realisasi Maqashid Syariah pada Lembaga Filantropi Islam (Pengentasan Kemiskinan melalui BUMMas: Asset Based Community Development Approach) - Kusmilawaty, Kusmilawaty; Majid, M Shabri Abd; Harahap, Isnaini (Jurnal Ilmiah Ekonomi Islam, 2024)
The article aims to know how the mechanism of BUMMas establishments as poverty alleviation efforts with Asset Based Community Development Approach for the realitation of maqashid syariah in Islamic filantrophy institution. The research run by descriptive studies with qualitative analysis. Source of data this research from interview with Rumah Zakat and BUMMas Managements in Sumatera Utara, observation, and documentation studies. The result of study show that The mechanism for establishing BUMMas carried out by Islamic philanthropic institutions as an effort to eradicate poverty using an Asset Based Community Development approach is as follows: Rumah Zakat observes the resources and potential of the village. Human Capital is identified based on skills, expertise and educational background. Social capital is identified based on the closeness of relationships, networks, communities, and also prevailing habits or customs. Physical capital is identified based on existing infrastructure. Financial capital is identified based on the standard of living or income of potential beneficiaries. And environmental capital is identified based on the location where the Beneficiaries live; Rumah Zakat provides various business provisions and training to BUMMas. Also collaborates with the government through related agencies for business development. Rumah Zakat carries out guidance and monitoring of BUMMas by recruiting Inspiration Volunteers from community leaders on a regular and scheduled basis. With the success of BUMMas, the concept of maqashid sharia can be realized from all aspects, especially the economy. Hifz al-din (guarding religion), hifz al-nafs (guarding the soul), hifz al-maal (guarding wealth), hifz al-nasl (guarding descendants), and hifz al-aql (guarding reason).